Burma : aspects of a hidden culture - Hooy Kaye Museum, Brussel (Brussel : Hooy Kaye Museum Brussel, 2004)
The opening exhibition "Burma: aspects of a hidden culture" is built around a private collection that was established around the beginning of the 1990's. This in itself is already an interesting topic for the simple reason that very few museums have sizeable collections on the country that is today known as Myanmar. This can be explained by the fact that most Southeast Asian cultures for long have been considered to be minor art forms derived from India and/or China.
Exhibition "Burma : aspects of a hidden culture", in het Hooy Kaye Museum Brussel. 2004-04-02. 2004-08-07. verlengd tot 2004-11-27
Engels
boek